The Effectiveness of Cognitive-Behavioral Therapy on Pain Intensity, Childhood Trauma, Perfectionism, and Psychological Flexibility in Patients with Chronic Pain - Alizadeh, Parviz; Kooshki, Shirin; Tarvirdizadeh, Hajar (Health Nexus, 2024)
Chronic pain can significantly impact an individual’s health status and quality of life, leading to a decrease in health-related quality of life. This study aimed to determine the effectiveness of cognitive-behavioral therapy (CBT) on pain intensity, childhood trauma, perfectionism, and psychological flexibility in patients with chronic pain. This applied and quasi-experimental study employed a pre-test, post-test, and follow-up design with a control group. The statistical population included all chronic pain patients attending pain clinics in Tehran, totaling 198 individuals. From this population, 50 patients were selected through purposive sampling based on inclusion and exclusion criteria and randomly assigned to either the CBT group (25 individuals) or the control group (25 individuals). Data were collected using the West Haven-Yale Multidimensional Pain Inventory (Kerns et al., 1985), the Childhood Trauma Questionnaire (Bernstein et al., 2003), the Multidimensional Perfectionism Scale (Frost et al., 1990), and the Acceptance and Action Questionnaire (Bond et al., 2011). CBT for chronic pain was conducted in seven 60-minute group sessions over two months, based on the treatment package (Kelly Lamb, 2018). Data were analyzed using repeated measures ANOVA with SPSS.22 software. The results indicated that CBT was effective on pain intensity (P<0.001), childhood trauma (P<0.001), perfectionism (P<0.001), and psychological flexibility (P<0.001) in patients with chronic pain. It can be concluded that CBT is effective on pain intensity, childhood trauma, perfectionism, and psychological flexibility in patients with chronic pain. This therapy can be used to reduce the psychological problems of individuals suffering from chronic pain.